2015
DOI: 10.1016/j.memsci.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Fouling mitigation in membrane distillation processes during ammonia stripping from pig manure

Abstract: Over time fouling leads to membrane wetting. This is the biggest obstacle to widespread use of membrane distillation (MD) for ammonia removal from animal slurry. Feed pretreatment and cleaning strategies of membrane surfaces are the most common methods to prevent or diminish fouling phenomena. This study investigates preliminary fouling of polypropylene (PP), and polytetrafluoroethylene (PTFE) membranes. A model manure solution was used as feed. In addition, cleaning efficiencies with deionized water, NaOH/cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 65 publications
(92 reference statements)
1
33
1
Order By: Relevance
“…This technique is commonly used for characterization of MD membranes. As an example, Zarebska, et al [103] used AFM morphological analysis to understand the observed decrease in contact angle and surface charge of PTFE and PP membranes used in MD. The three-dimensional AFM pictures of virgin and fouled PTFE and PP membranes with model manure solution and pig manure after sieving with MF and UF showed that the foulants accumulate in the "valleys" leading to a drop of surface roughness [103].…”
Section: Atomic Force Microscopy (Afm)mentioning
confidence: 99%
See 4 more Smart Citations
“…This technique is commonly used for characterization of MD membranes. As an example, Zarebska, et al [103] used AFM morphological analysis to understand the observed decrease in contact angle and surface charge of PTFE and PP membranes used in MD. The three-dimensional AFM pictures of virgin and fouled PTFE and PP membranes with model manure solution and pig manure after sieving with MF and UF showed that the foulants accumulate in the "valleys" leading to a drop of surface roughness [103].…”
Section: Atomic Force Microscopy (Afm)mentioning
confidence: 99%
“…It is a measure of the magnitude of electrostatic repulsion or attraction between particles. In general, zeta potential is a key indicator of the stability of colloidal particles and it is a good method to describe double-layer properties of colloidal dispersions [15,103]. Various factors affect the zeta potential such as the concentration, composition, temperature and pH of the solution as well as the membrane surface properties (i.e., charge, roughness, chemical heterogeneity, etc.)…”
Section: Zeta Potentialmentioning
confidence: 99%
See 3 more Smart Citations